HUBUNGAN OBESITAS SENTRAL DAN AKTIVITAS FISIK DENGAN KEJADIAN DIABETES MELITUS TIPE 2 DI PUSKESMAS III DENPASAR UTARA: THE RELATION OF CENTRAL OBESITY AND PHYSICAL ACTIVITY WITH THE INCIDENCE OF TYPE 2 DIABETES MELLITUS IN NORTH DENPASAR HEALTH CENTER III - Trisnadewi, Ni Wayan; Widarsih, Ni Luh; Pramesti, Theresia Anita (Stikes Wira Medika Bali, 2019)
Introduction: Type 2 diabetes mellitus is a diabetes that most occurs and can caused by several factors such as central obesity and physical activity. This study aimed to determine the relation of central obesity and physical activity with the incidence of type 2 diabetes mellitus in North Denpasar Health Center III. Method: This research used descriptive correlation with cross sectional approach, conducted with 51 respondents used purposive sampling. Results: Lambda test results on relation of central obesity and incidence of type 2 diabetes mellitus showed that 29 respondents with type 2 diabetes mellitus and central obesity obtained p value = 0.031 (p<0.05), that means H0 was rejected and there’s relation between central obesity and incidence of type 2 diabetes mellitus with r value=0.529. Lambda test results on the relation of physical activity and incidence of type 2 diabetes mellitus showed 27 respondents with type 2 diabetes mellitus and low physical activity obtained p value =0.04 (p<0.05) that means H0 was rejected there’s relation between physical activity and incidence of type 2 diabetes mellitus with r value = 0.529. The result indicated a moderate and positive correlation. Discussion: The decreased of visceral adipose in central obesity and high physical activity can increase the sensitivity of insulin receptors.